Upaya-Upaya Meningkatkan Kemampuan Menyimak Peserta Didik - Mutasim, Imam (Jurnal Likhitaprajna, 2020)
The Indonesian syllabus is explicitly focused on all four language skills integrally. However. In fact in the process of teaching and learning the Indonesian language is still focused on developing reading, writing and speaking skills. Listening skills are rarely implemented by teachers in learning activities. Listening skills are never programmed. If listening skills were taught, this was just a coincidence. Though listening skills are essential for the overall development and learning of Indonesian.